(3GdEeJGY h GdeDGfSI (B:s (3GdLRA GdChd CKGQ COHjI (B/s - (3GdJhMjOj, CHhMjGfs; (3fhjhGJs ((3GdLRGFQ (B:s (3ehae ddfTQh GdJhRjY (B;(3GdeDSSI GdhWfjI ddafhf GdeWHYjI ,s, 1989)
(3cJGH YXje GdaGFOI ZRjQ GdeGOI eeJY eDfS ceG jhMj HPdc YfhGfg Cdag CHh MjGf dUOjbg hhdj fYeJg CHj GdhaGA eMeO Hf eMeO Hf jMj GdHhRLGfj GdQjGj GdTgjQ jUa dg ajg eLGdS GdhRjQ GHf SYOGf h jQhj dg eGOGQ ajgG ef GMGOjK JJfGhd dGHMK eNJdaGdbVGjG GdYdejI h GdafjI ef GOH h dZI h abg h adSaI h Yde GLJeGY h SjGSI h Ydhe ObjbI h (B((3GdEeJfGY h GdeDGfSI(B) (3PNjQI dG JfaP h cfR ef cfhR GdGOH GdYQHj HeGOJg GdKQjI h GSdhHg GdfGUY h efWbg Gdbhj(B. s
Keywords: (3CHj MjGf GdJhMjOjs